Análise da contaminação microbiana de dispositivos acrílicos confeccionados em laboratórios de prótese dentária - Temóteo, Guilherme de Alencar (2014)
The possible presence of potentially pathogenic microorganisms in denture newly arrived from prosthetic laboratories should be considered. This study evaluated the level of bacterial and fungal contamination of specimens of acrylic resin made in 14 dental laboratories registered with the Regional Council of Dentistry of Ceará, Fortaleza. Each laboratory was asked to fabricate 10 specimens of acrylic resin, from standard models of sterile silicone addition, unaware of the research objectives. Specimens received from laboratories were placed in individual tubes containing BHI broth, incubated at 37°C for 48 hours and then removed, washed and placed in sterile saline and stirred for microbial detachment. The suspension obtained was diluted (1:100, 1:1000) and plated on blood agar plates, and Sabouraud Dextrose Agar and Agar HiCrome ICU by incubation for 48 hours at 37°C. The number of colony forming units (CFU) bacterial and fungal viable was obtained, besides the identification and quantification of some species of bacteria, comparing the laboratory by means of the Kruskal-Wallis and Dunn (α = 0.05) tests. There was contamination originating from all laboratories analyzed, with a mean CFU counts of 101438 bacteria and 71047 fungi. Pseudomonas spp was the most prevalent microorganism identified (p < 0.05). It was concluded that there is a risk of contamination with potentially pathogenic bacteria and fungi in prosthetic devices newly arrived from dental laboratories.